An Evaluation of South Africa's Application of the OAU Refugee Definition - Schreier, Tal Hanna (Refuge: Canada's Journal on Refugees, 2008)
This paper undertakes an analysis of South Africa’s application of the OAU Convention’s expanded refugee definition. It finds that in the first stage of South Africa’s refugee status determination process, government officials tasked with individually determining refugee status seemingly make use of the OAU Convention’s refugee definition and basic country of origin information in a unique form of prima facie refugee determination. In this regard, improved training of officials is essential in order to ensure that the appropriate level of protection to all asylum seekers is afforded in terms of the definition. At the South African Refugee Appeal Board level, however, due to the in-depth nature of the decisions rendered, the OAU refugee definition is more correctly, yet cautiously, utilized to provide protection to persons fleeing indiscriminate widespread disruption of public order or generalized violence. This research is the first of its kind to analyze select decisions of the South African Refugee Appeal Board.